2020
DOI: 10.1371/journal.ppat.1009121
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 facilitates rapid expulsion of the parasitic nematode Strongyloides ratti from the intestine via ILC2- and IL-9-driven mast cell activation

Abstract: Parasitic helminths are sensed by the immune system via tissue-derived alarmins that promote the initiation of the appropriate type 2 immune responses. Here we establish the nuclear alarmin cytokine IL-33 as a non-redundant trigger of specifically IL-9-driven and mast cell-mediated immunity to the intestinal parasite Strongyloides ratti. Blockade of endogenous IL-33 using a helminth-derived IL-33 inhibitor elevated intestinal parasite burdens in the context of reduced mast cell activation while stabilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
(129 reference statements)
2
24
0
Order By: Relevance
“…When mast cells are exposed to bacterial toxins, they recruit neutrophilic granulocytes and release pro-inflammatory mediators such as IL −6, TNF-α, and lipid mediators, thereby eliminating the bacteria and reducing bacterial colonization [ 5 , 8 ]. Moreover, the importance of mast cells in parasitic infections has also been demonstrated in Strongyloides ratti , where the mast cell deficient model showed impaired parasite defense and slowed response to the alarmin IL −33 [ 9 ]. Although mast cell activation is essential for the body’s defense against infection, inappropriate activation can lead to deleterious results.…”
Section: The Role Of Mast Cells In Diseasementioning
confidence: 99%
“…When mast cells are exposed to bacterial toxins, they recruit neutrophilic granulocytes and release pro-inflammatory mediators such as IL −6, TNF-α, and lipid mediators, thereby eliminating the bacteria and reducing bacterial colonization [ 5 , 8 ]. Moreover, the importance of mast cells in parasitic infections has also been demonstrated in Strongyloides ratti , where the mast cell deficient model showed impaired parasite defense and slowed response to the alarmin IL −33 [ 9 ]. Although mast cell activation is essential for the body’s defense against infection, inappropriate activation can lead to deleterious results.…”
Section: The Role Of Mast Cells In Diseasementioning
confidence: 99%
“…Given that ILC2s were previously shown to mediate protective immune responses against different intestinal helminths i.e. in S. ratti infection through mast cell activation and N. brasiliensis infection through involvement in maintenance of alternatively activated macrophages ( 15 , 35 ), we speculated that ILC2s are also involved in protective immune responses against L. sigmodontis infection in semi-susceptible C57BL/6 mice. To investigate the role of ILC2s during L. sigmodontis infection by depletion experiments, we used T and B cell-deficient Rag2 -/- C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are a main target of IL-9, which serves as a growth factor for these cells and also in uences their function 36,37 . The present study demonstrated that mast cell accumulation in the lung tissue of HDM-challenged mice was clearly attenuated by IL-9 de ciency, and this was supported by the reduction of mMCP-1 in the lung tissue homogenate of the experimental animals.…”
Section: Discussionmentioning
confidence: 99%